This fight is our fight : the battle to save America's middle class - Warren, Elizabeth (New York : Metropolitan Books/Henry Holt and Company, 2017)
Senator Elizabeth Warren has long been an outspoken champion of America's middle class, and by the time the people of Massachusetts elected her in 2012, she had become one of the country's leading progressive voices. Now, at a perilous moment for our nation, she has written a book that is at once an account of how we built the strongest middle class in history, a scathing indictment of those who have spent the past thirty-five years undermining working families, and a rousing call to action. Warren grew up in Oklahoma, and she has never forgotten how difficult it was for her mother and father to hold on at the ragged edge of the middle class. An educational system that offered opportunities for all made it possible for her to achieve her dream of going to college, becoming a teacher, and, later, attending law school. But for many, these kinds of opportunities are gone, and a government that once looked out for working families is instead captive to the rich and powerful. Seventy-five years ago, President Franklin Roosevelt and his New Deal ushered in an age of widespread prosperity. In the 1980s, President Ronald Reagan reversed course and sold the country on the disastrous fiction called trickle-down economics. Now, with the election of Donald Trump -- a con artist who promised to drain the swamp of special interests and then surrounded himself with billionaires and lobbyists -- the middle class is being pushed ever closer to collapse. This Fight Is Our Fight tells eye-opening stories about her battles in the Senate and vividly describes the experiences of hard-working Americans who have too often been given the short end of the stick. Elizabeth Warren has had enough of phony promises and a government that no longer serves its people -- she won't sit down, she won't be silenced, and she will fight back.
The disappearing middle class -- A safer economy -- Making, and breaking, the middle class -- The rich and powerful tighten their grip -- The moment of upheaval.
Includes bibliographical references (pages 271-315) and index.
Keywords: 2000-2099; Middle class -- United States; Economic history; Economic policy; Fiscal policy; Middle class -- Economic conditions; Politics and government; Social conditions; BIOGRAPHY & AUTOBIOGRAPHY / Political; POLITICAL SCIENCE / American Government / Legislative Branch; POLITICAL SCIENCE / Political Process / Political Parties; United States -- Economic policy -- 2009-; United States -- Economic conditions -- 2009-; United States -- Social conditions -- 1980-; United States -- Politics and government -- 2009-2017.; United States